Effects of different woods in barbecuing: Consumers' sensory perception and liking of grilled chicken meat. (January 2023) - Piochi, Maria; Cabrino, Giorgia; Torri, Luisa
Graphical abstract: Highlights: Type of wood strongly influenced the sensory properties and liking of grilled meat. STRAWBERRY wood gave the most peculiar and intense flavor attributes to meat. OAK, OLIVE, and GRAPEVINE woods gave less intense sensations to meat. Two clusters with opposite preferences influenced by the wood type were found. Future wood certifications could valorize the grilling process in restaurants/pubs. Abstract: The sensory effects of grilling wood on consumers' response are poorly understood, despite their potentiality in diversifying dishes. This study investigated both the effects of six materials (beech tree wood, Turkey oak wood, Sangiovese grapevine wood, olive wood, strawberry tree wood, charcoal briquettes) used to grill chicken breast meat on liking and sensory perception and consumers' interest in using wood for grilling. A consumer test was conducted (n = 99 subjects, 45% males, aged from 18 to 65 years), applying a Rate-All-That-Apply test, a liking test, and a questionnaire exploring the interest, the perceived value and the sustainability of wood as part of the food processing. The type of wood clearly affected the consumers' sensory perception and acceptability of meat. Strawberry tree wood was the most connoted and divisive sample. Turkey oak, olive tree and Sangiovese grapevine woods were associated to milder sensory profile. Two clusters were found (respectively with 54% participants in Cl1 and 46% in Cl2), with opposite preferences: while Cl2 preferred meat grilled with the most connotating wood (Strawberry tree wood) characterized by bitterness while Cl1 on the opposite preferred meat grilled with the milder woods. Consumers showed a high interest for grilling material, wood origin and wood botanical species, independently from the cluster. Strawberry tree wood was the material that most strongly connotated grilled meat and thus the most divisive one in terms of liking. Different varieties of wood and certified sustainable wood can valorize the grilling process in food services.